1994
DOI: 10.1016/0042-6989(94)90295-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-range dichoptic interactions in the human visual cortex in the region corresponding to the blind spot

Abstract: Tbe region of tbe visual field of one eye tbat corresponds to tbe blind spot of the coutraIatera1 eye is beiieved to be monocular. We measured dicboptic coatour interaction in this region of tbe visual field in bumans by having observers report tbe orientation of a test letter "T" presenH to tbis region, in the presence of thud&g T's presented around tbe blind spot of the fellow eye. A large drop in performance was seen because of tbe Bauks, showing clearly tbe existence of dicboptic contour interaction in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
0
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 48 publications
2
36
0
2
Order By: Relevance
“…Some researchers have suggested important roles for interactions between the facilitatory and inhibitory regions within neuronal receptive fields in early visual areas or interactions between neurons via long-range horizontal connections (Flom, Heath, & Takahashi, 1963;Polat & Sagi, 1994;Tripathy & Levi, 1994). Others have suggested that crowding, particularly foveal crowding, is a form of spatial-frequency masking or contrast masking (Chung, Levi, & Legge, 2001; or is related to the physical properties of the stimulus (Hess, Dakin, & Kapoor, 2000).…”
mentioning
confidence: 99%
“…Some researchers have suggested important roles for interactions between the facilitatory and inhibitory regions within neuronal receptive fields in early visual areas or interactions between neurons via long-range horizontal connections (Flom, Heath, & Takahashi, 1963;Polat & Sagi, 1994;Tripathy & Levi, 1994). Others have suggested that crowding, particularly foveal crowding, is a form of spatial-frequency masking or contrast masking (Chung, Levi, & Legge, 2001; or is related to the physical properties of the stimulus (Hess, Dakin, & Kapoor, 2000).…”
mentioning
confidence: 99%
“…Another view argues that surface-specific neuronal activity in the visual system occurs at a relatively early stage of visual processing and that the activity is topographically correlated with the perceptual consequence of filling-in. Although some psychophysical studies support the former idea (Cumming and Friend, 1980), other studies support the latter (Tripathy and Levi, 1994;Murakami, 1995).…”
Section: Neural Mechanisms Of Filling-in At the Blind Spotmentioning
confidence: 72%
“…Most importantly, they found that the targetflanker distance required for this crowding follows the cortical magnification of the striate cortex, and thus spans a constant distance in V1 regardless of eccentricity. These estimations by Levi and colleagues, along with a study using dichoptic interaction in the blind spot by Tripathy and Levi (1994) and the more recent calculation by Pelli (2008) based on letter crowding put the cortical distance of crowding somewhere between 3 and 8 mm in V1. This is broadly consistent with the estimated extent of horizontal connections in the striate cortex (ϳ6 -8 mm; Gilbert 1992;Stettler et al 2002).…”
mentioning
confidence: 93%
“…Primary visual cortex (V1) has been implicated in some of the earliest behavioral studies on crowding Tripathy and Levi 1994), a view that was reiterated in some of the recent theories (Nandy and Tjan 2012; Pelli 2008). Specifically, Levi and colleagues found that vernier threshold was elevated by flankers placed far from the vernier target.…”
mentioning
confidence: 96%
See 1 more Smart Citation